ANALISIS YURIDIS KEABSAHAN AKTA PERJANJIAN KAWIN YANG DIBUAT DIHADAPAN NOTARIS YANG TIDAK DI REGISTRASI (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 598 PK/PDT/2016 Tanggal 24 Nopember 2016) - AMRIZAL AMRIZAL (PREMISE LAW JURNAL, 2018)
Dosen Pembimbing:1. Prof. DR. hasim Purba, Sh, MHum2. DR. Yefrizawati, SH, MHum3. DR. Utary maharany Barus, SH, MHum The result of the research shows that the Ruling of Judicial Review No. 598 PK/Pdt/2016 which revokes Marriage Contract No. 200 on July 8, 1994 made and signed before Eko Handoko Widjaja, S.H., Notary in Malang, since it is not registered in the Residential Affairs and Civil Registry Office, is correct and accurate. In the Ruling, the Marriage Contract is considered contrary to and violating against Law No. 1/1974 in Chapter V, Article 29, paragraph 1, Article 152 in conjunction with Article 147 of the Civil Code because it is registered. The legal consequence of joint property has to be distributed equally.Keywords: Certificate, Validity, Marriage Contract, Registration